Perspectives on cervical cancer screening and prevention: challenges faced by providers and patients along the Texas–Mexico border. (July 2019) - Boom, K; Lopez, M; Daheri, M; Gowen, R; Milbourne, A; Toscano, P; Carey, C; Guerra, L; Carvajal, JM; Marin, E; Baker, E; Fisher-Hoch, S; et al.
Background: The Rio Grande Valley (RGV) and Laredo regions located along the Texas–Mexico border consist of seven counties with a population of approximately 1.5 million people and a high uninsured rate (33.5%). Cervical cancer mortality in these border counties is approximately 30% higher than the rest of Texas. The RGV and Laredo areas were studied to better understand the state of access to cervical cancer prevention services along the Texas–Mexico border. Methods: Data on the population served and the services provided were analyzed to determine the gap between cervical cancer screenings recommended versus those received. Through interviews, we gathered the perspectives of 16 local stakeholders regarding cervical cancer screening for underserved individuals in the region. Findings: It is estimated that 69, 139 uninsured women aged 21–64 years in the RGV/Laredo per year are recommended to undergo cervical cancer screening with Papanicolaou (Pap) and/or human papillomavirus (HPV) testing, but only 8941 (12.9%) Pap tests are being performed by the Federally Qualified Health Center (FQHC) serving uninsured women in these regions. Systemic barriers identified include insufficient provider clinical capacity, the high cost of healthcare, and uncertainty about government funding sources. Patient barriers identified include inadequate knowledge on navigating the local healthcare system, low health literacy, lack of money and childcare, an inability to miss work, limited transportation, and fear of deportation. Conclusion: Decreasing the disparity between cervical cancer screening services provided and those recommended requires addressing the barriers, identified by local experts, which prevent uninsured women from accessing care. These challenges are being addressed through ongoing programs and collaborations.